The effect of using three teaching strategies for conceptual change to address the misunderstanding of mathematical concepts among middle school students (Journal of the College of Basic Education, 2022)
Learning mathematics is a problem identified by many researchers, educators, teachers and students themselves for all academic levels, such as the study (Bottag 1993) globally, the study (Al-Karsh 1998), the study (Abu Amira 2000) in the Arab world, the study (Bushra 1998), the study (Abdul Hussein 1998) and (Al-Saadi 2002). locally.